3x+6=-5-1x

Simple and best practice solution for 3x+6=-5-1x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6=-5-1x equation:


Simplifying
3x + 6 = -5 + -1x

Reorder the terms:
6 + 3x = -5 + -1x

Solving
6 + 3x = -5 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
6 + 3x + x = -5 + -1x + x

Combine like terms: 3x + x = 4x
6 + 4x = -5 + -1x + x

Combine like terms: -1x + x = 0
6 + 4x = -5 + 0
6 + 4x = -5

Add '-6' to each side of the equation.
6 + -6 + 4x = -5 + -6

Combine like terms: 6 + -6 = 0
0 + 4x = -5 + -6
4x = -5 + -6

Combine like terms: -5 + -6 = -11
4x = -11

Divide each side by '4'.
x = -2.75

Simplifying
x = -2.75

See similar equations:

| 3x^3+4x^4-6x^5-9x^6+14x^7-6x^8+x^9=0 | | ((a^4)/(2a^2-4a^4))*((8a^3+1)/(2a+4a^2)) | | 7(3x-9)=34 | | x-15=31 | | 5(7x-9)=20 | | 14-3x=-16 | | 6/7x-1/4x+10=11/14 | | 1/4(204a)=6a | | 80000=x+x+.11x | | (5-x)/4x-20 | | K=2j-3 | | X^2-12=-20 | | (2/3)x+6=-3 | | 3w(2w-7)=0 | | x/(-5)=17 | | x+2.5=0.38 | | X+2+3x-10=16 | | 18+3x=5x+10 | | 2(2d-1)=4d-7 | | X/3-2=70 | | 0=2x^2-11x+21 | | 3z/2+1/4=7/8 | | 4x+9=10x | | 1-3/5x=4/10x | | 7=8x+6 | | 2(7x-6)=3(1-3x) | | 45+63x(45+55)33-88= | | 5.4=18y | | 5.4/2y=9 | | (9)w=54 | | 2.5(-3x+2)=.75x+6 | | 4(4+1)=x+10 |

Equations solver categories